Strategy for Implementing Performance Architecture in the Performance Accountability System of Government Agencies (SAKIP) in Central Sulawesi - Mappatoba Andi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
Performance architecture is a critical field within information technology that helps organizations design, implement, and optimize technology in alignment with their business objectives. Every organization relies on various information systems to support its operational functions, and performance architects play a vital role inenhancing the efficiency and effectiveness of organizational performance. This study employs a qualitative research methodology, utilizing literature, regulatory, and policy data, alongside the analysis of the written or spoken words of stakeholders, to assess the application of performance architecture within the Government Agency Performance Accountability System (SAKIP) in the public sector. Policy analysis is conducted by examining existing theories and regulations related to performance architecture in SAKIP and its implementation within the Central Sulawesi Government. From the analysis, it is clear that the strategy for implementing performance architecture in the Central Sulawesi Government plays a crucial role in improving government organization performance. This is evident in the adoption of the West Java Integrated Government Agency Performance Management (JAPATI) model, which has been adapted into the Central Sulawesi version, the Integrated Performance Accountability System (SALIARA). The SALIARA application is publicly accessible, allowing citizens to view the Governor’s performance, regional apparatus performance, and budget allocations. Based on the findings, the following steps are essential for the Central Sulawesi Provincial Government: formulate policies and strategies for implementing National Bureaucratic Reform, develop Integrated Performance Management Guidelines, create Performance Tree guidelines for cascading, alignment of Regional Development Planning, and Regional Apparatus Development Planning within the Central Sulawesi Provincial Government, formulate policies for Regional Apparatus and individual reward/punishment systems, and establish a Governor’s Regulation to govern the implementation of the SALIARA application.